Fluctuating running speed during 10-km running elevates physiological strain - Sumi, D.; Takii, Y.; Abe, S.; Sakaguchi, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Although it is anecdotally believed that fluctuating running speed during competition has a negative impact on running performance, its influence on physiological strain remains unclear. Therefore, the purpose of the present study was to determine the effect of fluctuating running speed during 10-km running on physiological strain compared with constant running speed.